2013
DOI: 10.1007/s10620-013-2833-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bispectral Index Monitoring During Balanced Propofol Sedation for Colonoscopy: A Prospective, Randomized Controlled Trial

Abstract: BIS and clinical sedation scores, MOAA/S scores, showed a high level of correlation. However, no significant efficacy was observed in the BIS group who underwent outpatient colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
0
17
1
1
Order By: Relevance
“…assessing recovery time or patients' or endoscopists' satisfaction. [12][13][14][15][16] It has been demonstrated that intraoperative BIS monitoring facilitates the titration of anesthetic agents. Thus, it has the potential to decrease the use of anesthetic agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…assessing recovery time or patients' or endoscopists' satisfaction. [12][13][14][15][16] It has been demonstrated that intraoperative BIS monitoring facilitates the titration of anesthetic agents. Thus, it has the potential to decrease the use of anesthetic agents.…”
Section: Discussionmentioning
confidence: 99%
“…11 Previous studies on the use of BIS for sedation monitoring during colonoscopy mostly focused on decreasing the amount of sedative agent administered and the recovery time required, and on assessing the patient's or endoscopist's satisfaction. [12][13][14][15][16] The influence of depth of anesthesia on postoperative impairment of cognitive function among surgical patients has already been investigated through BIS monitoring. 17 Various medications have been compared in studies assessing postoperative impairment of cognitive function subsequent to procedures such as colonoscopy and endoscopic retrograde cholangiopancreatography (ERCP).…”
Section: Introductionmentioning
confidence: 99%
“…Contrasting with previous results in flexible bronchoscopy [2], gastroscopy [3] and colonoscopy [4], Grendelmeier et al [1] found that conscious sedation with propofol was more risky than with midazolam given the higher incidence of hypoxemia (pulsed arterial oxygen saturation <90%: 27 vs. 4%) and hypotensive episodes (systolic blood pressure <90 mm Hg: 82 vs. 40%). These results also contradict the excellent safety profile that we reported in medical thoracoscopy when bispectral index monitoring, a clinical scale of sedation depth and end-tidal capnography were used by nonanesthetist nurses to more precisely titrate the intravenous administration of propofol and opiates [5].…”
Section: Financial Disclosure and Conflicts Of Interestmentioning
confidence: 64%
“…When compared with procedural sedation, BIS monitoring has several advantages. It is an objective method of monitoring sedation that has been widely used in various surgical and endoscopic procedures: a BIS value of about 70 provides effective sedation for procedures like gastrointestinal endoscopy inspection and endoscopic submucosal dissection (Yu et al, 2013). BIS can also provide continuous monitoring of sedation depth, enabling the anesthesiologist to alter the depth of sedation in pace with the procedures.…”
Section: Bis-guided Sedation Is Feasible In Tavimentioning
confidence: 99%